2015
DOI: 10.3389/fnhum.2014.01055
|View full text |Cite
|
Sign up to set email alerts
|

Brain computer interface to enhance episodic memory in human participants

Abstract: Recent research has revealed that neural oscillations in the theta (4–8 Hz) and alpha (9–14 Hz) bands are predictive of future success in memory encoding. Because these signals occur before the presentation of an upcoming stimulus, they are considered stimulus-independent in that they correlate with enhanced memory encoding independent of the item being encoded. Thus, such stimulus-independent activity has important implications for the neural mechanisms underlying episodic memory as well as the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 59 publications
1
42
0
Order By: Relevance
“…In most brain regions sampled, we observed strongly heterogeneous responses, with a mixture of recording sites exhibiting relative HFA increases following rewards and other recording sites exhibiting relative HFA increases following penalties. Because HFA is thought to reflect the summed activity of a large population of local neurons (Nir et al, 2007; Ray et al, 2008; Miller, 2010; Burke et al, 2015), our results suggest that neuronal populations in most human brain regions encode outcome valence in a heterogeneous manner (i.e., some neurons show relative increases following rewards, whereas others show relative increases following penalties). Such heterogeneous encoding patterns have been demonstrated in cortical regions by several monkey single-unit studies during reinforcement learning (Matsumoto et al, 2007; Asaad and Eskandar, 2011), and have been suggested as a reason why univariate functional neuroimaging studies may not be able to detect many cognitive signals when averaging activity within brain regions (Wallis and Kennerley, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…In most brain regions sampled, we observed strongly heterogeneous responses, with a mixture of recording sites exhibiting relative HFA increases following rewards and other recording sites exhibiting relative HFA increases following penalties. Because HFA is thought to reflect the summed activity of a large population of local neurons (Nir et al, 2007; Ray et al, 2008; Miller, 2010; Burke et al, 2015), our results suggest that neuronal populations in most human brain regions encode outcome valence in a heterogeneous manner (i.e., some neurons show relative increases following rewards, whereas others show relative increases following penalties). Such heterogeneous encoding patterns have been demonstrated in cortical regions by several monkey single-unit studies during reinforcement learning (Matsumoto et al, 2007; Asaad and Eskandar, 2011), and have been suggested as a reason why univariate functional neuroimaging studies may not be able to detect many cognitive signals when averaging activity within brain regions (Wallis and Kennerley, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…In our experiment, we did not find a particular frequency range that was associated with accuracy or error correction; however, in examining the EEG response across the entire range of frequencies, the model could predict the response in a subsequent session. Now that we know that EEG error prediction is possible, we can use this information to design future studies that will more directly test this relationship (see, e.g., Burke et al, 2015; Salari and Rose, 2016). These possibilities include presenting naming trials only when task-appropriate activity is present, as in Salari and Rose (2016).…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on prior evidence that changes in alpha and theta waves occurring prior to stimulus presentation can predict successful memory encoding and recognition (e.g., Fell et al, 2011; Merkow et al, 2014), Burke et al (2015) designed an experiment in which the participant’s own EEG response was used to trigger stimulus presentation. The authors hypothesized that if words were only presented when the participant was in an optimal brain state for learning, memory encoding and recall would improve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the advancements in BCI application for motor recovery after stroke, the literature on BCI systems that target cognitive deficits is limited (Burke et al, 2014). To outline reasonable approaches, BCI researchers should refer to current treatment strategies for neuropsychological deficits and to the wide literature on neurofeedback approaches for cognitive enhancement.…”
Section: Cognitive Rehabilitationmentioning
confidence: 99%